2005
DOI: 10.1002/gcc.20222
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a single‐step mechanism in the origin of hyperdiploid childhood acute lymphoblastic leukemia

Abstract: High hyperdiploidy (>50 chromosomes) in childhood acute lymphoblastic leukemia (ALL) is characterized by nonrandom multiple trisomies and tetrasomies involving in particular chromosomes X, 4, 6, 8, 10, 14, 17, 18, and 21. This characteristic karyotypic pattern, the most common in pediatric ALL, may arise via a tetraploid state with subsequent loss of chromosomes, by sequential gains of chromosomes in consecutive cell divisions, or by simultaneous gain of chromosomes in a single mitosis. These alternatives may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 48 publications
10
74
0
Order By: Relevance
“…Several studies have shown that wUPIDs are present in 25-30% of cases from this subgroup (23)(24)(25), in line with our finding of 27%. We have proposed previously that this overrepresentation may reflect the underlying mechanism by which the hyperdiploidy originates (2), in particular because the previous studies have not shown wUPID for specific chromosomes (23)(24)(25). However, our present data indicate that there also is a nonrandom pattern of wUPIDs in high hyperdiploid ALL (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have shown that wUPIDs are present in 25-30% of cases from this subgroup (23)(24)(25), in line with our finding of 27%. We have proposed previously that this overrepresentation may reflect the underlying mechanism by which the hyperdiploidy originates (2), in particular because the previous studies have not shown wUPID for specific chromosomes (23)(24)(25). However, our present data indicate that there also is a nonrandom pattern of wUPIDs in high hyperdiploid ALL (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…[Samples from parents had been obtained as part of a previous investigation (23).] The analysis could be performed in three of the cases with wUPID9 (cases 3, 8, and 50) and in two of the cases with wUPID11 (cases 1 and 50).…”
Section: Qf-pcrmentioning
confidence: 99%
“…17 They confirm, together with a high frequency of related IGH rearrangements and of three or more rearrangements in almost 45% of cases, the notion that the nondisjunction of chromosomes leading to an HeH karyotype affects a cell at the beginning of IGH recombination. 23,24 In line with this notion, the other half of HeH leukemias with no more than two IGH rearrangements supposedly have duplicated a chromosome 14 with a preexisting (V H )DJ H rearrangement that is not modified anymore thereafter. Additional features from SB also fit in this concept, as the vast majority of cases lack IGH germ-line configuration or deletions.…”
Section: Discussionmentioning
confidence: 91%
“…Among the 78 high hyperdiploid ALLs investigated, 26 (33%) harbored mutations of FLT3, The karyotypes of these cases have been previously published (Heim et al, 1990;Kö hler et al, 1996;Andreasson et al, 1998Andreasson et al, , 2000Paulsson et al, 2003Paulsson et al, , 2005Paulsson et al, , 2006Schaad et al, 2006 …”
Section: Resultsmentioning
confidence: 97%
“…However, considering that the hyperdiploid clone may already be present at birth but that there is a latency period of several years before overt leukemia (Panzer-Grü mayer et al, 2002;Maia et al, 2003Maia et al, , 2004, it seems unlikely that the tri-and tetrasomies alone are sufficient for leukemogenesis. Furthermore, it has been shown that a single abnormal mitosis underlies all chromosomal gains in most cases, indicating that the cell giving rise to the hyperdiploid clone harbored other genetic abnormalities, inducing the aberrant cell division and/or allowing it to survive such a drastic and sud-den aneuploidy (Onodera et al, 1992;Paulsson et al, 2003Paulsson et al, , 2005. G-banding, fluorescence in situ hybridization (FISH), conventional comparative genome hybridization (CGH), array-based CGH, and single nucleotide polymorphism array analyses only detect structural chromosomal changes in a subset of pediatric high hyperdiploid cases (Elghezal et al, 2001;Kristensen et al, 2003;Moorman et al, 2003;Paulsson et al, 2005Paulsson et al, , 2006Davidsson et al, 2006Davidsson et al, , 2007Mullighan et al, 2007;Strefford et al, 2007).…”
Section: Introductionmentioning
confidence: 99%